Physiological response in professional female soccer players: Comparison between small-sided games and laboratory exercise testing - Apriantono, T.; U`Lum, W. B.; Ramania, N. S.; Winata, B. (Journal of Human Sport & Exercise, 2025)
The aim of this study was to describe the physiological characteristics and energetic requirements of small-side games (SSG) in female players by means of ambulatory gas exchange measurements using a breath-by-breath (B × B) approach. Eight female professional soccer players participated in this study. This study was divided into two sessions: laboratory exercise testing and SSG field testing. Both tests were performed using simultaneous gas exchange measurements. The incremental ramp exercise test was performed using portable metabolic carts breath by breath (B×B) and a treadmill, to measure the maximum oxygen uptake (VO2max) and maximum heart rate (HRmax) of each player. In the SSG field test, the metabolic carts (B×B), was used during SSG to measure oxygen uptake (VO2), average heart rate (HRave), breath frequency (fB), minute ventilation (VE), energy expenditure (EE), and heart Rate and O2 Pulse (VO2/HR). Activity profiles were assessed by professional technical coaches (n = 2). A total of 152 passes were included in the four-a-side SSG analysis. Specifically, 85.53% of the total passes were categorized as successful passes and 14.47% were categorized as failed passes. VO2 during SSG was 83.90% of the VO2max, and HRave during SSG was 84.42% of the HRmax. The independent t-test showed a difference between blood lactate levels post-SSG and blood lactate after the incremental ramp-like exercise [p = .001; F = 97.294]. Four-a-side SSG have sufficient physiological demands for female players, characterized by achieving the minimum standard of physiological response with maximum aerobic capacity.